Ulugombakia, a new eucerine bee from Malaya (Hymenoptera: Apoidea: Apidae). - Baker, Donald Burton (Contributions to Entomology = Beiträge zur Entomologie, 2003)
Ulugombakia platytarsus gen. nov., sp. nov., is described from Malaya. Tetralonia erythrocera Cameron, 1909, and Tetralonia kohatensis Cockerell, 1917, are synonymized with Eucera cassandra Nurse, 1904, = Tetraloniella cassandra (Nurse, 1904), synn. nov., comb. nov. A lectotype is designated for Eucera cassandra Nurse. Keywords Eucerini, taxonomy, synonymy, biogeogeography, SE Asia, biodiversity. Nomenclatural Acts Ulugombakia Baker, 2003 (Apidae), gen. n. erythrocera Cameron, 1909 (Tetralonia), syn. n. of Eucera (Synhalonia) cassandra Nurse, 1904 kohatensis Cockerell, 1917 (Tetralonia), syn. n. of Eucera (Synhalonia) cassandra Nurse, 1904 platytarsus Baker, 2003 (Ulugombakia), spec. n.